Albidosides H and I, two new triterpene saponins from the barks of Acacia albida Del. (Mimosaceae). Issue 8 (18th April 2018) - Tchoukoua, Abdou; Kuiate Tabopda, Turibio; Konga Simo, Ingrid; Uesugi, Shota; Ohno, Misa; Kimura, Ken-ichi; Kwon, Eunsang; Momma, Hiroyuki; Shiono, Yoshihito; Ngadjui, Bonaventure Tchaleu
Abstract: Two new triterpene saponins, albidosides H (1 ) and I (2 ), along with the three known saponins were isolated from the barks of Acacia albida . Their structures were elucidated on the basis of extensive 1D- and 2D-NMR studies and mass spectrometry. Albidosides H (1 ) and I (2 ) were assayed for their cytotoxicity against HeLa and HL60 cells using MTT method. Abstract :